Getting a head start: capital inheritance and the labour market entry of Finnish business graduates - Haltia Nina; Isopahkala-Bouret Ulpukka; Mutanen Heli (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Previous studies have associated participation in higher education with the formation of middle-class advantages. Studies have shown that graduates from affluent family backgrounds gain more advantages from graduate degrees and secure better job opportunities than their less privileged counterparts. Drawing on the Bourdieusian framework, this study uses qualitative interview data (n = 29) to examine how recent business graduates mobilise economic, cultural and social capital for their entry into the Finnish labour market. The context of the Finnish welfare society brings novel insights to research on the inheritance of different forms of capital. Our findings reveal that although middle-class students do have a head start in entry to the graduate labour market, the Finnish society and higher education system even out social inequalities in graduate employment as working-class students may utilise institutional resources, socialise with peers and accumulate work experience to cross structural and dispositional barriers.